Social Network Analysis of an Agricultural Center: Stakeholders and the Transfer of Information. Issue 1 (2nd January 2022) - Cramer, Mary E.; Habecker, Patrick; Wendl, Mary; Sayles, Harlan; Rautiainen, Risto; Dombrowski, Kirk
ABSTRACT: We conducted a social network analysis (SNA) of Central States Center for Agricultural Safety and Health (CS-CASH) to describe stakeholder networks for agricultural Research and Education/Outreach. This was a two-phase study. First, the Leader Survey went to N = 9 CS-CASH leaders to identify their key stakeholders. Next, the Stakeholder Survey was sent to these stakeholders to learn about their stakeholder collaborations, interactions, and communications. The Pajek Network Analysis measured SNA metrics for density, centrality, betweenness, k-core, and created the sociograms. The Leader Survey had a 100% response rate and generated N = 337 unique stakeholders. Most were researchers (44%) and educators (20%), with a primary sphere of influence in Nebraska-only (40%). The Stakeholder Survey had 46% response rate, and generated N = 199 names in the extended Education/Outreach network and N = 140 in the extended Research network. Stakeholders in both networks were employed mostly in universities/schools (61%) or non-profits (15%). Both networks had a single main component and 7/9 CS-CASH leaders had central roles in these components. CS-CASH is well positioned in the extended stakeholder networks based on SNA metrics. Stakeholders utilize CS-CASH resources, and they seek and exchange information with its leaders. To strengthen knowledge transfer, it will be useful to build on connections with stakeholders outside academia.